Northern News - North America, Arctic Institute of (ARCTIC, 1949)
The news items include: 1) a new twin-screw icebreaker that will be built for the Canadian Dept. of Transport for supplying northern stations; 2) the launching of the C.D. Howe, a new Canadian Eastern Arctic Patrol ship; 3) the laying of the keel of the new Royal Canadian Navy icebreaker which is under construction; 4) archaeological work on Cornwallis Island near Resolute Bay; 5) the trial of two young Netsilik Eskimo men on charges of assisting the suicide of a woman, who was the mother of one of the men, with tuberculosis; 6) the announcement by the U.S. Transportation Corps that they are sending modified half-track vehicles north to test their usefulness; 7) various articles about Greenland affairs including the creation of funds for increased cultural relations between Greenland and Denmark, population statistics of Greenland, the establishment of air transportation between Greenland and Denmark, the construction of vacation homes for convalescing Greenlandic children, and the free distribution of fresh vegetables - a gift from Danish market gardeners.